Respostas
respondido por:
1
Resposta:
58/3
Explicação passo-a-passo:
= 5x² - y/2 • 2xy/3
= 5.2² - (-1)/2 . 2.2.(-1)/3
= 5.4 + 1/2 . (-4)/3
= 20 - 4/6 (:2)/(:2)
= 20 - 2/3
= (3.20 -2)/3
= (60-2)/3
= 58/3
o valor de x = 2
o valor de y = -1
R.: 58/3
respondido por:
1
Resposta: 58/3
= 5x² - y/2 • 2xy/3
= 5.2² - (-1)/2 . 2.2.(-1)/3
= 5.4 + 1/2 . (-4)/3
= 20 - 4/6 (:2)/(:2)
= 20 - 2/3
= (3.20 -2)/3
= (60-2)/3
= 58/3
o valor de x = 2
o valor de y = -1
R.: 58/3
Explicação passo-a-passo:
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
8 anos atrás